Redefining corporate social responsibility - Crowther, David; Seifi, Shahla (Emerald Publishing Limited, 2018)
It can be argued that Corporate Social Responsibility has been universally accepted and is gradually being incorporated into the planning and activities of all organisations around the world. The subject of CSR has been debated and theorized over the last 25 years, to such an extent that we can claim to have arrived at a theoretical understanding as well as an understanding of what constitutes best practice. The aspects which merit attention have also been generally agreed at least according to the majority of researchers. Present attention is directed towards such things as sustainability. This book, however, takes a different approach and argues that there has been a divergence between what academics understand by corporate social responsibility and what is practiced in the world both in business and elsewhere within society.Through a series of studies of aspects of CSR from around the world, it re-examines the topic though the lenses of various disciplines and cultures. It shows that the subject is much wider than is generally perceived and that CSR is evolving in a way which has not been generally recognized within the academic community. Invaluable to researchers and students in the field, this book contributes towards a much-needed redefinition of CSR.
Includes index.
Keywords: Social responsibility of business.; Corporate governance.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books